Workplace Safety and Health Practices and Employee Commitment in the Uganda Manufacturing Industry: A Case Study of Century Bottling Company Limited - Aminsi Asadhawaire (Uganda Christian University, 2024)
The study explores the workplace safety practices on employees' commitment in Uganda's manufacturing industry and focuses on Century Bottling Company Limited. This work was guided by the following objectives: to identify workplace safety and health practices at Century Bottling Company; to assess the nature of employee commitment at the organization; and to investigate the causes of workplace hazards at Century Bottling Company Limited. A cross-sectional research design was used with the integration of quantitative and qualitative research methodologies. Data were collected from 75 respondents using questionnaires and 4 key informants through interviews. Data analysis used frequencies, percentages, means and standard deviations. Results indicated that Century Bottling Company included safety rules and procedures, safety training and management support included in work practices on safety and health in the workplace. The study also identified machinery malfunction, chemical spills and failure to comply with safety precautions as major causes of occupational hazard. In this study, it was also established that employees express their commitment to the organization basing on affective, continuance, and normative dimensions. From these findings, this study suggests that the management of Century Bottling Company is supposed to invest in a holistically safety training program for all its employees since this is an integral approach toward achieving the desired state of safety culture within the organization. In addition, the safety rules and procedures should also be reviewed and updated periodically so that their relevance and effectiveness in the dynamic work environment will be a reality. Secondly, strict monitoring of compliance with safety regulations and the necessary acts of discipline in case of any form of non-compliance is also imperative. These could equally involve periodic safety inspections, reviews of incident reports, and dealing proactively with cases of non-compliance.
Undergraduate research